English Education in Distress? - Eggins, Heather (International Higher Education, 2013)
In an attempt to introduce some elements of the market into higher education in England, the present government has introduced tuition fees up to a maximum of £9000 a year, along with a system which allows universities to accept as many high performing students as they wish. However, the number of available places remains strictly controlled. Added to this is an ongoing policy of fair access, where every university is expected to attract agreed numbers from disadvantaged groups. The ensuing problems caused by disparate policies are unsettling the system.